The role of cGAMP via the STING pathway in modulating germinal center responses and CD4 T cell differentiation - Yoon, Mijung; Choi, Yurim; Wi, Taeuk; Choi, Youn Soo; Choi, Jinyong (Frontiers in Immunology, 2024)
Germinal center (GC) responses are essential for establishing protective, long-lasting immunity through the differentiation of GC B cells (BGC) and plasma cells (BPC), along with the generation of antigen-specific antibodies. Among the various pathways influencing immune responses, the STING (Stimulator of Interferon Genes) pathway has emerged as significant, especially in innate immunity, and extends its influence to adaptive responses. In this study, we examined how the STING ligand cGAMP can modulate these key elements of the adaptive immune response, particularly in enhancing GC reactions and the differentiation of BGC, BPC, and follicular helper T cells (TFH). Employing in vivo models, we evaluated various antigens and the administration of cGAMP in Alum adjuvant, investigating the differentiation of BGC, BPC, and TFH cells, along with the production of antigen-specific antibodies. cGAMP enhances the differentiation of BGC and BPC, leading to increased antigen-specific antibody production. This effect is shown to be type I Interferon-dependent, with a substantial reduction in BPC frequency upon interferon (IFN)-β blockade. Additionally, cGAMP's influence on TFH differentiation varies over time, which may be critical for refining vaccine strategies. The findings elucidate a complex, antigen-specific influence of cGAMP on T and B cell responses, providing insights that could optimize vaccine efficacy.